Mainstreaming Gender in Global Climate Governance - Flavell, Joanna (Taylor & Francis, 2023)
This book explores the role of feminist activists in The United Nations Framework Convention on Climate Change and highlights the progress they have made in mainstreaming gender as a key issue in global climate governance.